Extending the Theory of Planned Behaviour to Understand Entrepreneurial Intention Among Female University Students in Saudi Arabia: The Role of Entrepreneurship Education - Belgaroui, Rym; Shili, Aicha (Journal of Posthumanism, 2025)
Purpose – This study explored how various factors distinctly affect the entrepreneurial intentions of business female students, by providing theoretical and practical contributions to researchers working in this area and other parties to understand and translate the outcomes from the study into real life situations. Design/methodology/approach–Primary research is conducted through a survey questionnaire distributed to a sample of 243 students in September to October 2024. The study’s data were analyzed using the statistical software SPSS 25 and AMOS 25. To measure the internal consistency reliability of the scale, two methods were applied, which are Cronbach’s alpha test and the “composite reliability” (CR) index. Findings – The results show that there is significant and positive relationship between attitude and perceived behavioral control and the entrepreneurial intention. Our study confirms the positive effect of Risk-taking, Financial support and entrepreneurial Education on entrepreneurial intention but suggests no relationship between subjective norms and entrepreneurial intentions. Research limitations/implications – Our research of entrepreneurial intentions is limited by the inclusion of entrepreneurial students in our model, who may serve as future entrepreneurs. Future study could apply our model to actual entrepreneurs at various business stages, in keeping with recent studies that emphasize the significance of entrepreneurial life cycles.Originality/value – This study indicates that universities should create educational policies and structures to effectively inspire entrepreneurs. This study founded that providing students with adequate knowledge and motivation towards entrepreneurship will increase the likelihood of young people being involved in venture creation.